2003
DOI: 10.1590/s1413-78522003000300002
|View full text |Cite
|
Sign up to set email alerts
|

Estudo anatômico e artroscópico do ligamento femoropatelar medial

Abstract: Os autores estudaram em joelhos de 11 cadáveres a presença do ligamento femoropatelar medial.Em 6 joelhos o estudo foi anatômico por dissecção e secção seriada das peças anatômicas.Em 5 joelhos o estudo foi artroscópico pela visibilização nos joelhos do ligamento encontrado nos seis joelhos estudados anatomicamente. Em todas as peças anatômicas foi possível a dissecção da estrutura ligamentar descrita como o ligamento femoropatelar medial e nos cinco joelhos estudados sob visão artroscópica a visibilização e i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 8 publications
1
9
0
3
Order By: Relevance
“…These instruments, usually written in English language, assess the impact of these dysfunctions on patients' quality of life (12) . Overall, studies addressing knee are based on objective aspects of surgical (13) , drug (14) , clinical (15) , treatment, as well as on joint anatomy (16) . Little emphasis has been placed on activities of daily life of patients with knee conditions.…”
Section: Discussionmentioning
confidence: 99%
“…These instruments, usually written in English language, assess the impact of these dysfunctions on patients' quality of life (12) . Overall, studies addressing knee are based on objective aspects of surgical (13) , drug (14) , clinical (15) , treatment, as well as on joint anatomy (16) . Little emphasis has been placed on activities of daily life of patients with knee conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Aikanen et al (28) , in 1993, propose the reconstruction of the MPFL with the tenodesis of the last eight cm distal to the adductor magnus m. tendon, since they consider that most of injuries occur at the femoral side (epicondyle); They assess 14 knees with 12 good outcomes and two moderate outcomes. In 2001, Camanho and Viegas (29) initiated a research series, in which anatomy and biomechanical aspects of the Medial Patellofemoral Ligament are studied in cadavers. Arendt et al (19) believe that the ligament is united in elongation and it needs to be re-tensioned, except in cases of multifocal injury.…”
Section: Discussionmentioning
confidence: 99%
“…Cash and Hughston (12) published a classic study where 399 patients with acute patellofemoral dislocation were studied; although demonstrating a percentage of 50% -70% of good outcomes with conservative treatment, they reported no recurrences in patients surgically treated through medial capsule repair. In anatomical and biomechanical studies (3,13,14) of the MPFL there was a clear trend by authors to treat acute patellofemoral dislocations by repairing the MPFL. Sallay et al (17) , Boden et al (16) , Ahmad et al (15) presented their series with MPFL repair with no reports of dislocation recurrences.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment is still controversial in literature; the immediate reconstruction, or the conservative treatment are discussed behaviors. From the 1990s on, some authors (3,4,5) reported their results on treating acute patellar dislocation by repairing the medial patellofemoral ligament (MPFL), described by Warren and Marshall (6) . The understanding of this ligament's anatomy and biomechanics and its repair have occasioned better and smoother outcomes to the surgical treatment of the acute patellar dislocation.…”
Section: Introductionmentioning
confidence: 99%